Long COVID and the impact on quality of life post-infection - Pedro Sousa Riola, João; Lima Lopes Pontes, Luiza; Noronha Araujo dos Santos, Sofia; Leite Rosa Pinheiro da Silva, Juliana; Fiorin Sprone, Flavia; Penha Pereira, Luciano (Seven Editora, 2023)
Covid-19 is a viral infection caused by the Sars-CoV-2 virus that started a worldwide pandemic in 2019, being responsible for causing inflammatory syndromes that can affect all human systems, especially the pulmonary one. Long covid is related to the prolonged time in which the individual is affected by the virus, and may extend for months and even year after infection, leaving systemic sequelae. DOI: https://doi.org/10.56238/tfisdwv1-159